Intelligence in the Madani Era and its Usage in the Contemporary Period - Al Azhari, Abdul Wahab Jan (Journal of Islamic and Religious Studies, 2020)
This research deals with the security situation and the collection of information during the Jihad in the Madani era, and how it was influential and important. The Prophet (PBUH) established a state that's administrative, advocacy, and security elements have been advanced and completed. No one thinks that security in its modern forms has been absent from the awareness of the Prophet (peace and blessings of Allah be upon him) and his great companions, and the researcher extracted the need to collect information about the opponents of State and preparation for them. There several studies on the subject but did not address the aspects mentioned in this research, and deals with all the ancient and modern works on the issue of the composition of the spies which are the core of my research and indicate the positions of the biography of the Prophet (PBUH). There is a research journal namely “Dialmi” in Arabic published approximately 55 research Articles entitled Spies and impact in Wars in the life of the Prophet (PBUH). However, it discussed the military side only and did not vary in the classification of information. The research article concludes with a comprehensive analysis of the aspects dealt with in terms of methodology and its characteristics.